2018
DOI: 10.3389/fpls.2018.01886
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hormonal Application Regulates the Occurrence of Wheat Tillers by Changing Endogenous Hormones

Abstract: Plant hormones play important roles in regulating the occurrence of crop tillers. However, little is known about the relationships and the underlying mechanisms between endogenous hormones and the occurrence of wheat tillers induced by exogenous hormones. In this study, two winter wheat cultivars, Xinong 979 and Xiaoyan 22, were used to investigate the effects of the exogenous application of indole-3-acetic acid (IAA) and zeatin (Z) on the occurrence of wheat tillers and investigate underlying mechanisms regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 39 publications
3
53
0
3
Order By: Relevance
“…As reported, the higher spike number was the consequence of a higher tiller number, which was positively correlated with the content of endogenous zeatin in the field-grown wheat after exogenous hormonal application (Cai et al, 2018). Moreover, the authors showed that IAA application inhibited the occurrence of tillers, by changing the ratios of IAA and ABA to zeatin.…”
Section: Discussionmentioning
confidence: 59%
“…As reported, the higher spike number was the consequence of a higher tiller number, which was positively correlated with the content of endogenous zeatin in the field-grown wheat after exogenous hormonal application (Cai et al, 2018). Moreover, the authors showed that IAA application inhibited the occurrence of tillers, by changing the ratios of IAA and ABA to zeatin.…”
Section: Discussionmentioning
confidence: 59%
“…Higher levels of endogenous IAA might cause an inhibitory effect, so the optimum endogenous level must be controlled. Cai et al (2018) found that at 3 days after exogenous application of SA, the endogenous SA reached the maximum and subsequently decreased until it reached the level of control plants at 7 days later.…”
Section: Introductionmentioning
confidence: 91%
“…The regulation of endogenous hormones may effectively increase the survival rate of florets [17][18][19][20]. Previous studies have shown that cytokinin effectively controls plant growth and development by regulating the proliferation and differentiation of plant cells, such as promoting bud growth and fruit development, delaying senescence, and regulating the transduction of nutritional signals [21][22][23]. 6-benzylaminopurine (6-BA) is a synthetic cytokinin that can also promote cell division and improve plant growth and development [24].…”
Section: Introductionmentioning
confidence: 99%